PENGARUH PERSEPSI WAJIB PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK PADA PENGUSAHA MUDA DI KOTA PAREPARE DIMODERASI OLEH NILAI BUDAYA BUGIS - Damis, Sariana; Su'un, Muhammad; Tenriwaru, Tenriwaru (Economos : Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of subjective norms, behavioral control and attitudes on compliance with paying local taxes, the influence of subjective norms, behavioral control and attitudes on cultural values of Bugis, the influence of cultural values on compliance with paying local taxes the influence of subjective norms, behavioral control and attitudes towards compliance to pay local taxes through Bugis cultural values. This research was conducted in the City of Parepare. The time of this research was started from March to August 2020. The population in this study were young entrepreneurs in the city of Parepare, who are members of the Parepare City Young Entrepreneurs Association. Sampling using saturated sampling technique or census, the sample in this study was 150 respondents. The results of the study 1) Subjective norms have no significant effect on compliance with paying local taxes, 2) Behavioral control has a positive and significant effect on compliance with paying local taxes, 3) Attitudes have no positive and significant effect on compliance with paying local taxes. 4) Subjective Norms have no negative and insignificant effect on the cultural values of Bugis, 5) Behavioral control has a positive and significant effect on the cultural values of Bugis, 6) Attitudes have a positive and significant effect on the cultural values of Bugis, 7) Cultural values of Bugis have an effect on compliance with paying taxes 8) Based on the calculation of path analysis it can be concluded that subjective norms have no positive and insignificant effect on compliance with paying local taxes through cultural values of Bugis, 9) Based on the calculation of path analysis it can be concluded that behavioral control has a positive and significant effect on compliance with paying local taxes through Bugis cultural values, 10) Based on the calculation of path analysis, it can be concluded that attitudes have a positive and significant effect on compliance with paying local taxes through Bugis cultural values.